2008
DOI: 10.1016/j.gep.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic gene expression of Lin-28 during embryonic development in mouse and chicken

Abstract: The Caenorhabditis elegans heterochronic gene lin-28 regulates developmental timing in the nematode trunk. We report the dynamic expression patterns of Lin-28 homologues in mouse and chick embryos. Whole mount in situ hybridization revealed specific and intriguing expression patterns of Lin-28 in the developing mouse and chick limb bud. Mouse Lin-28 expression was detected in both the fore-limb and hindlimb at E9.5, but disappeared from the forelimb at E10.5, and finally from the forelimb and hindlimb at E11.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…Previous studies showed that Lin28a mRNA and protein are expressed widely in all three germ layers during early development of mouse and chicken (Yang and Moss, 2003;Yokoyama et al, 2008). In Xenopus, most zygotic gene expression commences after the MBT.…”
Section: Expression Of X Tropicalis Lin28a and Lin28bmentioning
confidence: 98%
“…Previous studies showed that Lin28a mRNA and protein are expressed widely in all three germ layers during early development of mouse and chicken (Yang and Moss, 2003;Yokoyama et al, 2008). In Xenopus, most zygotic gene expression commences after the MBT.…”
Section: Expression Of X Tropicalis Lin28a and Lin28bmentioning
confidence: 98%
“…At the cellular and organismal level, the functions and pattern of expression of lin-28 are, in broad terms, strikingly consistent between C. elegans and vertebrates. Like in nematodes, the mammalian orthologs of lin-28 (Lin28A and Lin28B) are expressed during early developmental stages, mostly in cell populations undergoing active proliferation, and polymorphism of LIN28B are associated with variations in the timing of human development (Yang and Moss 2003;Yokoyama et al 2008;Ong et al 2009). Deletion of Lin28A causes reduced body size in mice, while its over-expression produces abnormally large animals (Zhu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The LIN28 protein contains two RNA-binding domains: a cold-shock domain (CSD) and retroviral-type CCHC zinc knuckles. Lin28 is expressed in embryonic stem (ES) cells and in diverse tissues within the embryo, including the developing nervous system, and in developing tissues of the adult (Richards et al, 2004;Yang and Moss, 2003;Yokoyama et al, 2008). As in C. elegans, levels of LIN28 protein are high in developing tissues and decrease as differentiation proceeds (Moss and Tang, 2003;Yang and Moss, 2003).…”
Section: Introductionmentioning
confidence: 99%